1991
DOI: 10.1002/ecja.4410740210
|View full text |Cite
|
Sign up to set email alerts
|

Relation between spacing and receiving efficiency of finite rectenna array

Abstract: I n t h e rectenna a r r a y used f o r r e c t i f ic a t i o n of t h e microwaves received on t h e ground i n t h e s o l a r power s a t e l l i t e system, i t i s required t h a t t h e rectenna elements have a high dc power conversion e f f i c i e n c y and t h a t t h e element spacing i s optimized so t h a t t h e a r r i v i n g microwave power i s received e f f i c i e n t l y and t h e number of e l ements can be reduced.I n t h i s paper, a microwave r e c t i f i e r is f a b r i c a t e d i … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 1 publication
0
13
0
Order By: Relevance
“…A study of the rectenna array problem was carried out at Waseda University [9] in Japan. However, it was limited only to the mutual coupling problem, that is, the relation between the element spacing and receiving efficiency of a finite rectenna array.…”
Section: Introductionmentioning
confidence: 99%
“…A study of the rectenna array problem was carried out at Waseda University [9] in Japan. However, it was limited only to the mutual coupling problem, that is, the relation between the element spacing and receiving efficiency of a finite rectenna array.…”
Section: Introductionmentioning
confidence: 99%
“…The absorption efficiency of the infinite rectenna array composed of the other antennas is formulated in the other paper [6,7]. Otsuka et al expanded the theory of the absorption efficiency of the infinite rectenna array to that of the finite rectenna array and carried out WPT experiment to confirm the absorption efficiency of the rectenna array [8]. The experimental results indicate that the absorption efficiency of the rectenna array can be close to 100 %.…”
Section: ⅱ Theorymentioning
confidence: 99%
“…The subarrays are of square arrangement of the element spacing of 0.7 wavelengths [Otsuka et al, 1990] as shown in Figure 2, and Figure 3 shows the measured patterns of the subarrays. Gains and XPIRs in the boresight direction of the subarrays are summarized in Table 1.…”
Section: Experimental Verificationmentioning
confidence: 99%